Atrial Arrhythmias Following Surgical AF Ablation: Electrophysiological Findings, Ablation Strategies, and Clinical Outcome. (2nd April 2014) - HUO, YAN; SCHOENBAUER, ROBERT; RICHTER, SERGIO; ROLF, SASCHA; SOMMER, PHILIPP; ARYA, ARASH; RASTAN, ARDAWAN; DOLL, NICOLAS; MOHR, FRIEDRICH‐WILHELM; HINDRICKS, GERHARD; PIORKOWSKI, CHRISTOPHER; GASPAR, THOMAS
Surgical Ablation Related Reentrant Tachycardia Background Intraoperative atrial fibrillation (AF) ablation during cardiac surgery is a well‐established treatment. However, tachycardia mechanisms, ablation strategies, and long‐term follow‐up of atrial arrhythmias (AA) following intraoperative AF ablation (AFA) have not been previously studied in a large cohort of patients. Objective Eighty‐two patients (48 male, median age of 65 years) with symptomatic recurrence of AA following intraoperative AFA underwent radiofrequency catheter ablation. Methods Regular atrial tachycardias (AT) were mapped using 3‐dimensional (3D) color‐coded entrainment/activation mapping and eliminated by linear ablation. Pulmonary vein (PV)‐isolation (PVI) was achieved in patients with left atrium‐PV (LAPV) conduction after AT elimination. Results In 85 (83%) out of a total of 103 regular ATs, the entire reentrant circuits were localized perimitrally (n = 27), around PVs (left PV [LPV] or right PV [RPV]; n = 9), around left atrial appendage (LAA; n = 1), on left‐sided atrial septum (n = 8), on atrioventricular nodal area (n = 1), on the posterior wall of LA (n = 1), along roof‐septum‐inferoposterior wall (n = 8), at coronary sinus ostium (n = 2), upper loop in RA (n = 1), and as cavotricuspid isthmus‐dependent reentrant ATs (n = 27). Sixty‐five (79%) patients received PVI. Noninducibility of any AT was reached at the end of all procedures. During a median follow‐up time of 18 months, 69 patients (87%) were free of AA. Conclusion Reentrant AT appears in the majority of patients with recurrence of AA following intraoperative AFA. Detailed 3D color‐coded entrainment mapping was successfully obtained in the majority of patients suffering from reentrant AT after intraoperative AFA, facilitated the accurate identification of the entire reentrant circuit and selection of optimal ablation lines.